A Study to Assess Knowledge and Practice of Menstrual Hygiene among the Teenage Students at Dnyanvilas College of Pharmacy, Dudulgaon - Hagawane, Divya; Kela, Punam; Patel, Esha (Journal of Pharmacy Practice and Community Medicine)
Introduction: Menstrual practices are still bounded by restriction due to taboos and social stigma. There is lack of knowledge among the adolescent girls regarding menstruation and menstrual hygiene which may lead to various reproductive tract infectious diseases. Awareness about menstruation right from childhood may help to eradicate this issue. Aim and Objectives: To assess the knowledge, practice of menstrual hygiene and restrictions faced by menstruating subjects during menstruation. Materials and Methods: A cross sectional observational study was conducted at Dnyanvilas College of Pharmacy, Dudulgaon, Pune. A Predesigned questionnaire was used to collect information regarding demographic details, type of absorbent used, storage of absorbent, frequency of changing sanitary pad, disposing method and personal hygiene. Also subject’s knowledge at the time of menarche was captured. Collected data was analyzed with the help of Microsoft Excel Sheet. Results: Out of 76 subjects 74% residing at rural area and 39.47% were unaware about the menstruation at the time of menarche. 26.32% subjects unsatisfactorily cleaning their external genital area and 89.47% were disposing the used pad in daily routine waste. 64.47% subjects were facing restrictions while attending family religious functions. Conclusion: The study revealed that menstrual hygiene was satisfactory among adolescents. Lack of sufficient knowledge and awareness among girls regarding menstruation can be improved by educating girls and their mothers. Educational programs should be conducted about the awareness of personal hygiene in schools and colleges that may help in increasing knowledge about menstruation and maintaining hygiene.
Keywords: Menstruation; Menstrual Hygiene; Sanitary Pad; Teenage girls; Awareness.